2007
DOI: 10.1167/iovs.07-0123
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Substance P in the Pathogenesis of Pterygia

Abstract: For the first time, this study showed the presence of NK(1) receptor in pterygia and that SP is a potent chemoattractant for pterygium fibroblasts and vascular endothelial cells, implying that SP may contribute to the shape of pterygia through its profibrogenic and angiogenic action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
1
27
0
2
Order By: Relevance
“…Stapleton and 8,15 . Indirect evidence of this interesting argument was reported by Chui and coworkers 16 . The authors found elevated presence of substance P preferred receptor in pterygia and demonstrated that this neuropeptide could contribute to the lesion shape though its profibrogenic and angiogenic action.…”
Section: Discussionmentioning
confidence: 78%
“…Stapleton and 8,15 . Indirect evidence of this interesting argument was reported by Chui and coworkers 16 . The authors found elevated presence of substance P preferred receptor in pterygia and demonstrated that this neuropeptide could contribute to the lesion shape though its profibrogenic and angiogenic action.…”
Section: Discussionmentioning
confidence: 78%
“…139 Inflammation is known to induce angiogenic pathways, which could result in neovascularization and contribute to pterygium growth. The angiogenic stimulation found in pterygium seems to be related to elevated levels of VEGF, low levels of thrombodopsin-1 (Tsp-1), 2 and a decrease in substance P, 140 which all promote the activity of the ETS-1 transcription factor that directly induces angiogenic activity. 25 VEGF acts as a chemokine in the initial step of basement membrane degradation during angiogenesis, which is a requisite process for the further locomotion and proliferation of endothelial cells, so they finally develop tubule-like structures.…”
Section: Angiogenesis and Lymphangiogenesismentioning
confidence: 99%
“…47 Furthermore, limbal focusing may also affect corneal nerves as they cross the limbus, allowing the possibility of neuropeptide involvement in pterygium pathogenesis and explaining corneal sensory alterations in pterygium patients. 48 If corneal nerves are implicated, their radial distribution may also help to explain pterygium shape.…”
Section: Peripheral Light Focusing and Pterygium Pathogenesismentioning
confidence: 99%
“…79 Another potential mode of action of cyclosporine is by the inhibition of the tachykinin NK1 receptors 80 that we have localized to infiltrating fibroblasts, mononuclear cells and the epithelia of pterygia. 48 In general terms, exposure of cells to UV induces activation of epidermal growth factor receptors (EGFRs) and subsequent downstream signaling through the mitogen-activated protein kinase pathways 65,66,81 that are partially responsible for expression of proinflammatory cytokines, and matrix metalloproteinases in pterygium cells. Growth factor receptors and associated signaling pathways are activated as an early response to UV exposure, occurring independently of ligand binding and believed to involve UVgenerated reactive oxygen species.…”
Section: Peripheral Light Focusing and Pterygium Pathogenesismentioning
confidence: 99%